Correlation of Understanding of Excretion System Material with Healthy Living Behavior of Class XI Science Students in MAN 3 Jember - Putri, Nahdiyah Avi Lutfiah; Nurlim, Risma; Nurlim, Idiawati (Aspirasi Masyarakat Intelektual Islam Nusantara, 2023)
The study's goal is to find a correlation between learning the excretory system material and the behavior of keeping a healthy lifestyle in class XI Science students at MAN 3 Jember. This research uses a non-experimental correlational quantitative approach. The population of this research was students of class XI IPA MAN 3 Jember, totaling 169 respondents. The samples taken were 118 respondents using the Simple Random Sampling technique. The data collection instruments used were tests on the variable understanding of the excretory system material and questionnaires with a Likert scale on the behavioral variable of maintaining a healthy life. Data analysis uses the product moment correlation test. Based on research data analysis, it shows that students' understanding of the excretory system material is categorized as moderate with a percentage of 84% and an average score of 12,3. Meanwhile, the behavior of maintaining a healthy life is in the medium category with a percentage of 59% and an average score of 27,5. The results of the product moment correlation analysis show that there is no relationship between understanding the excretory system material and the behavior of maintaining a healthy life in class XI Science students at MAN 3 Jember. The obtained significance value of 0.442 > 0.05, which means that Ha is rejected and H0 is accepted.